Does green economy contribute towards COP26 ambitions? Exploring the influence of natural resource endowment and technological innovation on the growth efficiency of China's regional green economy. (January 2023) - Wang, Xinbin; Wang, Zilong; Wang, Rong
Abstract: The COP26 conference pointed out that, in order to tackle climate change and promote global economic recovery, it is necessary to maintain a multilateral consensus, focus on practical actions, and accelerate green transformation. Whether a green economy can help achieve the goals of the COP26 has become the focus of attention of governments worldwide. Based on the data of 30 regions in China from 2009 to 2020, this study used the super-efficiency SBM model to evaluate green economy growth efficiency (GEGE) in China and also used the system GMM model to explore the impact of natural resource endowment and technological innovation on GEGE. The conclusions are as follows: (1) From 2009 to 2020, China's GEGE level was 0.606, which is a low-medium level. During the research period, the GEGE level showed an upward trend as a whole, with obvious regional differences, showing a decreasing trend from the eastern to central regions and the western region. (2) Natural resources can promote national GEGE. The "resource curse" was found to not exist from a country-wide perspective, and there was no inverted U-shaped relationship. Natural resources were found to inhibit the GEGE of the eastern and central regions with no inverted U-shaped relationship, but they were found to promote GEGE in the west of China with an inverted U-shaped relationship. (3) Technological innovation can improve the GEGE of the whole country and the three regions, and the effect is the largest in the western region. (4) In the eastern region, environmental regulation was found to promote GEGE, but inhibited the GEGE of the whole country and the other two regions. Economic development was found to have a positive effect on GEGE in all the regions. FDI can improve the GEGE of the whole country and the eastern and central regions, but had a negative impact on the west of China. Green finance was found to promote GEGE in the whole country and the eastern and western regions; although this was positive in the central region, it was not significant. The research in this paper has important theoretical reference significance for achieving the regional COP26 targets by using the green economic growth mode. Highlights: A fresh research under the cop26 target. Measure the growth efficiency green economy. Verify influencing factors of green economy growth efficiency. Make recommendations to improve the growth efficiency green economy.